The Implementation of Social Assistance Policies for Poor Communities in Kalora Village, Poso North Coastal District, Poso Regency - Mohammad Rusly Syuaib (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This research aims to determine the implementation of social assistance policies for the poor in Kalora Village, North Poso Coastal District, Poso Regency. Data for this research comes from two sources: primary data, collected directly through observation and interviews, and secondary data, which is in the form of papers from organizations involved in the research. The data obtained was then analyzed qualitatively. This study uses Edward III's theory, namely Communication, Resources, Disposition, Bureaucratic Structure, as a reference indicator in conducting research. The results of the study show that the implementation of social assistance policies for the poor in Kalora Village, North Poso Coastal District, Poso Regency, regarding the reach of the community in obtaining services, has been largely achieved, but there is a need to improve human resources with driving factors in terms of political leadership commitment and organizational capacity to help alleviate the burden of the community in the scope of operational work, especially in the delivery of programs to the community. Inhibiting factors in terms of the many players (actors) involved and the complexity inherent in the program itself will lead to overlapping policies that will confuse the issue of unclear regulations, and become the basis of misunderstanding between the village government and the community who will access the PKH assistance due to limited understanding.